49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3656
|View full text |Cite
|
Sign up to set email alerts
|

Flame Propagation from the Closed End of an Open-ended Tube: an analysis of the effects of fuel type, tube length, and equivalence ratio and an insight into flame dynamics

Abstract: Non-steady flame propagation in tubes has implications not only in explosion and hazard saftey, but also in the energy sector, as focus shifts towards pulsating constant volume combustion. Therefore, it is important to understand phenomena associated with these flames and their fine subtleties. These studies deal with flame propagation in tubes of small diameter and of varying lengths. The tubes are closed at the ignition end and open at the other. Natural gas-air as well as propane-air mixtures were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Two propagation modes are also seen here as previously reported. In two cases, extreme deceleration of the flame is observed due to the "tulip flame" phenomenon [18], a type of Rayleigh-Taylor instability, and subsequent coupling with the acoustic modes of the tube [19,20]. In the remaining cases, the flame does not exhibit said deceleration and continues to moderately accelerate.…”
Section: Resultsmentioning
confidence: 99%
“…Two propagation modes are also seen here as previously reported. In two cases, extreme deceleration of the flame is observed due to the "tulip flame" phenomenon [18], a type of Rayleigh-Taylor instability, and subsequent coupling with the acoustic modes of the tube [19,20]. In the remaining cases, the flame does not exhibit said deceleration and continues to moderately accelerate.…”
Section: Resultsmentioning
confidence: 99%
“…In numerical simulations of flame propagation assuming non-reflecting boundary conditions [28], oscillations due to flame inversion were identified showing that there is an additional source of oscillations different from acoustic feedback in these type of configurations. Furthermore, in [35], the authors compared predicted modes of oscillations due to acoustics with experimental results and found discrepancies that were attributed to the assumed reflection/transmission coefficients. On the other hand, the work in [34], showed that the observed oscillations depend on tube length and sound speed, showing a clear influence of acoustics.…”
Section: Front Velocity and Accelerationmentioning
confidence: 99%